Ecthyma gangrenosum due to Pseudomonas aeruginosa sepsis as initial manifestation of X-linked agammaglobulinemia: a case report - Haixia Huang; Ke Bai; Yueqiang Fu; Jin Yan; Jing Li (BMC, 2020)
Abstract Background X-linked agammaglobulinemia (XLA, OMIM#300,300), caused by mutations in the Bruton tyrosine kinase (BTK) gene, is a rare monogenic inheritable immunodeficiency disorder. Ecthyma gangrenosum is a cutaneous lesion caused by Pseudomonas aeruginosa that typically occurs in patients with XLA and other immunodeficiencies. Case presentation We report the case of a 20-month-old boy who presented with fever, vomiting, diarrhea, and ecthyma gangrenosum. Blood, stool, and skin lesion culture samples were positive for P. aeruginosa. A diagnosis of XLA was established, and the c.262G > T mutation in exon 4 of BTK was identified with Sanger sequencing. Symptoms improved following treatment with antibiotics and immunoglobulin infusion. Conclusions Primary immunodeficiency (i.e., XLA) should be suspected in male infants with P. aeruginosa sepsis, highlighting the importance of genetic and immune testing in these patients.